"They say it's fentanyl, but they honestly look like Perc 30s": Initiation and use of counterfeit fentanyl pills - Raminta Daniulaityte; Kaylin Sweeney; Seol Ki; Bradley N. Doebbeling; Natasha Mendoza (BMC, 2022)
Abstract Background Worsening of the overdose crisis in the USA has been linked to the continuing proliferation of non-pharmaceutical fentanyl (NPF). The recent wave of NPF spread in the USA has been fueled by an increased presence of counterfeit pills that contain NPF. This qualitative study aims to characterize the motivation and practices of counterfeit NPF pill initiation and use among individuals using illicit opioids in Arizona. Methods Between October 2020 and May 2021, semi-structured interviews were conducted with 22 individuals meeting the following eligibility criteria: (1) 18 years or older; (2) residence in Arizona; and (3) use of illicit opioids in the past 30 days and/or opioid use disorder treatment in the past 12 months. Participants were recruited through referrals by a harm reduction organization, craigslist ads, and referrals by other participants. Interviews were conducted virtually via Zoom. Qualitative interviews were transcribed and analyzed thematically using NVivo. Results Out of 22 participants, 64% were male, and 45% were ethnic minorities. Age ranged between 25 and 51 years old. Participants noted significant recent increases in the availability of counterfeit NPF pills ("blues," "dirty oxys") that were most commonly used by smoking. The majority indicated first trying NPF pills in the past year, and the first use often occurred in situations of reduced access to heroin or pharmaceutical opioids. Participant decisions to switch over to more frequent NPF pill use or to maintain some levels of heroin use were shaped by local drug availability trends and personal experiences with NPF effects. They were also influenced by conflicting views of social acceptability of pharmaceutical-like drugs, perceived harms of NPF in terms of overdose risks and increased difficulty of quitting, and perceived benefits of switching to the non-injection route of opioid administration (e.g., from injecting heroin to smoking NPF pills). Conclusion Our findings highlight the need for the implementation of novel policy, treatment, and harm reduction approaches to address the growing unpredictability of drug supply and NPF pill-specific risks, attitudes, and behaviors.